Analisis Perkembangan Kognitif Down Syndrome Melalui Media Puzzle Anak Usia 5-6 Tahun - Inayati Inayati; Ismatul Khasanah; Ellya Rakhmawati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The background of this study is that children with Down syndrome aged 5-6 years have an obstacle in cognitive development, especially the thought process seen when children use media, namely puzzle media.  The purpose of this study is to explain the extent of cognitive development in children with Down syndrome.  This study uses descriptive qualitative to find out data on cognitive development of children with Down syndrome in TK PGRI 64 Semarang. The data of this study were obtained through observation, interviews. The results of the research at PGRI 64 Kindergarten in Semarang showed that children with Down syndrome had the ability in learning process activities related to cognitive development, namely puzzle media, but it took a long time.